A great & godly adventure : the Pilgrims & the myth of the first Thanksgiving - Hodgson, Godfrey (PublicAffairs, 2006)
Refutes the legendary history of Thanksgiving by presenting a more authentic history of the Plymouth settlement, and explains the reasons behind the distortion of facts that gave rise to the holiday's traditions.